[18F]AV-1451 tau-PET and primary progressive aphasia - Josephs, Keith A. (Ann Neurol, 2018)
OBJECTIVES: To assess [(18)F]AV-1451 tau-PET uptake patterns across the primary progressive aphasia (PPA) variants (logopenic, semantic and agrammatic), examine regional uptake patterns of [(18)F]AV-1451 independent of clinical diagnosis, and compare the diagnostic utility of [(18)F]AV-1451, [(18)F]-fluorodeoxygluclose (FDG)-PET and MRI to differentiate the PPA variants. METHODS: We performed statistical parametric mapping of [(18)F]AV-1451 across 40 PPA patients (logopenic-PPA=14, semantic-PPA=13 and agrammatic-PPA=13) compared to 80 cognitively normal, PiB-negative controls, age and gender matched 2:1. Principal component analysis of regional [(18)F]AV-1451 tau-PET SUVR was performed to understand underlying patterns of [(18)F]AV-1451 uptake independent of clinical diagnosis. Penalized multinomial regression analyses were utilized to assess diagnostic utility. RESULTS: Logopenic-PPA showed striking uptake throughout neocortex, particularly temporoparietal, compared to controls, semantic-PPA and agrammatic-PPA. Semantic-PPA and agrammatic-PPA showed milder patterns of focal [(18)F]AV-1451 uptake. Semantic-PPA showed elevated uptake (left>right) in anteromedial temporal lobes, compared to controls and agrammatic-PPA. Agrammatic-PPA showed elevated uptake (left>right) throughout prefrontal white matter and in subcortical grey matter structures, compared to controls and semantic-PPA. The principal component analysis of regional [(18)F]AV-1451 indicated two primary dimensions, a severity dimension that distinguished logopenic-PPA from agrammatic-PPA and semantic-PPA, and a frontal-versus-temporal contrast that distinguishes agrammatic-PPA and semantic-PPA cases. Diagnostic utility of [(18)F]AV-1451was superior to MRI and at least equal to FDG-PET. INTERPRETATION: [(18)F]AV-1451binding characteristics differ across the PPA variants, and were excellent at distinguishing between the variants. [(18)F]AV-1451binding characteristics were as good or better than other brain imaging modalities utilized in clinical practice, suggesting that [(18)F]AV-1451 may have clinical diagnostic utility in PPA.